2003
DOI: 10.1016/s0168-6496(03)00070-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria associated with sardine (Sardina pilchardus) eggs in a natural environment (Ría de Vigo, Galicia, northwestern Spain)

Abstract: The present study was undertaken to describe the epiflora of the eggs of an important fishing species collected in a coastal zone. Microflora associated with sardine (Sardina pilchardus) eggs collected in the Ría de Vigo was examined from January to June 2000. The count was carried out in three different ways: a total direct count by epifluorescence, a heterotrophic bacteria count on marine agar (MA) and a total vibrio count on thiosulfate citrate bile sucrose (TCBS). It was observed that the counts of total b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…In this sense, bacteria have been isolated from the haemolymph of apparently healthy spider crab 1975; Tubiash, Sizemore & Colwell 1975;Welsh & Sizemore 1985;Davis & Sizemore 1982), the red swamp crawfish (Procambarus clarkii (Girard, 1852); Scott & Thune 1986) and the freshwater prawn (Macrobrachium rosenbergii (De Man, 1879); Brady & Lasso de la Vega 1992). As water was not sterilized at the entrance of the system, microbiological composition might be more affected during summer months compared with the rest of the year (Miguez & Combarro 2003), due to higher water temperature. All the above mentioned studies clearly support the need to know the bacterial populations in the haemolymph of healthy crustaceans to correctly interpret diagnostic results.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, bacteria have been isolated from the haemolymph of apparently healthy spider crab 1975; Tubiash, Sizemore & Colwell 1975;Welsh & Sizemore 1985;Davis & Sizemore 1982), the red swamp crawfish (Procambarus clarkii (Girard, 1852); Scott & Thune 1986) and the freshwater prawn (Macrobrachium rosenbergii (De Man, 1879); Brady & Lasso de la Vega 1992). As water was not sterilized at the entrance of the system, microbiological composition might be more affected during summer months compared with the rest of the year (Miguez & Combarro 2003), due to higher water temperature. All the above mentioned studies clearly support the need to know the bacterial populations in the haemolymph of healthy crustaceans to correctly interpret diagnostic results.…”
Section: Discussionmentioning
confidence: 99%
“…To survive in this highly competitive environment, microorganisms will exploit every possible niche available, including the colonization of nutrient‐rich surfaces of other marine organisms such as fish. Bacteria associated with the surface of marine fish eggs (Miguez & Combarro, 2003), larvae (Verner‐Jeffreys et al , 2003) and the surface and gut (for a review see Hansen & Olafsen, 1999) of a small number of adult fish species have previously been described using culture‐based methods. More recently, culture‐independent approaches have been applied to characterize the bacterial assemblage in the hind gut of marine herbivorous fish (Moran et al , 2005; Fidopiastis et al , 2006; Clements et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Other phenotypic studies from Galicia also rendered a low vibrio species diversity dominated by the Splendidus clade (Toranzo et al. 1993; Miguez and Combarro 2003).…”
Section: Discussionmentioning
confidence: 96%
“…2003). It has been found that the Vibrio species’ composition changes as the seawater temperature changes (Miguez and Combarro 2003); members of the Harveyi clade ( Vibrio core group) predominate when the temperatures are above 20°C, and those from the Splendidus clade when it is below that (Maeda et al. 2003).…”
Section: Discussionmentioning
confidence: 99%